2013
DOI: 10.1165/rcmb.2012-0304oc
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of Interleukin-25 and Extracellular Release of the Protein Is Regulated by Allergen Proteases in Airway Epithelial Cells

Abstract: Epithelial cells at mucosal surfaces are integral components of innate and adaptive immunity. IL-25 is reportedly produced by epithelial cells and likely plays vital roles in regulating type-2 immune responses. However, little is known regarding the mechanisms that control production and extracellular releases of IL-25. We hypothesized that proteases from the multiple allergens may induce IL-25 production in airway epithelial cells. In this study, we found that IL-25 is constitutively produced and detectable i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 46 publications
(25 reference statements)
0
57
0
1
Order By: Relevance
“…In addition, tissue stromal cells can express IL-17E. Human lung epithelial cells and murine primary type II alveolar epithelial cells express IL-17E following challenge with Aspergillus oryzae , ragweed allergens, and allergen proteases [41, 42]. Concordantly, IL-17E was detected at higher levels via immunohistochemistry (IHC) in the bronchial mucosa of asthmatics [43].…”
Section: Cellular Sources Of Il-17 Family Cytokinesmentioning
confidence: 99%
“…In addition, tissue stromal cells can express IL-17E. Human lung epithelial cells and murine primary type II alveolar epithelial cells express IL-17E following challenge with Aspergillus oryzae , ragweed allergens, and allergen proteases [41, 42]. Concordantly, IL-17E was detected at higher levels via immunohistochemistry (IHC) in the bronchial mucosa of asthmatics [43].…”
Section: Cellular Sources Of Il-17 Family Cytokinesmentioning
confidence: 99%
“…Unlike IL-33, which is stored in the nucleus, IL-25 is stored in and released from extra-nuclear cellular compartments. Kouzaki et al have reported that IL-25 is constitutively expressed in epithelial cells and is released upon exposure to proteases, such as trypsin, papain or in a more clinically relevant context, allergen proteases present in house dust mite (HDM) extract [21]. Given the immunological effects of IL-25, release of this cytokine by environmental proteases could have important implications in allergic disease.…”
Section: Recent Advances In Il-25 Biologymentioning
confidence: 99%
“…Effects of cockroach extracts on human airway epithelial cells have been described, that include the induction of cytokines and chemokines (IL-8, IL-25, IL-33, CCL20 and GM-CSF) [4244]. Some effects are mediated by proteases acting on protease-activated receptors (PAR-2) (see also Group 10 section) [45,46].…”
Section: Mechanisms Leading To Cockroach Allergymentioning
confidence: 99%